Some fixed point theorems in 1-M-complete fuzzy metric-like spaces. Issue 7 (16th November 2016) - Shukla, Satish; Gopal, Dhananjay; Roldán-López-de-Hierro, Antonio-Francisco
Abstract : Very recently, in order to unify the notions of fuzzy metric space and metric-like space, Shukla and Abbas introduced the concept of fuzzy metric-like space and proved some fixed-point results in this setting. In this article, we modify the notion of Cauchy sequence and completeness to generalize their results. Thus, we extend their theorems to a more general framework, which is also appropriate to generalize some recent, well-known results in this line of research. Furthermore, several examples are presented to illustrate the significance of our results.